2023
DOI: 10.1002/jbt.23389
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic acid‐downregulated long noncoding RNA ASMTL‐AS1 inhibits renal cell carcinoma growth via binding to HuR and reducing vascular endothelial growth factor expression

Abstract: It has been reported ursolic acid (UA), one of the naturally abundant pentacyclic triterpenes, possesses a wide range of biological activities including anti‐inflammatory, anti‐atherosclerotic, and anticancer properties. Renal cell carcinoma (RCC) is a severe malignancy due to its asymptomatically spreading ability. Our study aimed to investigate the role and molecular mechanism of UA in RCC. RCC cell proliferation, migration, invasion, and angiogenesis were assessed using 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…19 Ursolic acid inhibits renal cell carcinoma growth by binding to HuR and reducing the vascular endothelial growth factor expression. 47 Our results showed that TPP had a wide range of anticancer activities, and the inhibition of TPP on H460 cells was most obvious in a dose-dependent manner. TPP had a significant antiproliferative effect, and it could reduce cell viability to 50% within 48 h. This is closely linked to the anticancer activity of the triterpenes in TPP.…”
Section: Discussionmentioning
confidence: 58%
“…19 Ursolic acid inhibits renal cell carcinoma growth by binding to HuR and reducing the vascular endothelial growth factor expression. 47 Our results showed that TPP had a wide range of anticancer activities, and the inhibition of TPP on H460 cells was most obvious in a dose-dependent manner. TPP had a significant antiproliferative effect, and it could reduce cell viability to 50% within 48 h. This is closely linked to the anticancer activity of the triterpenes in TPP.…”
Section: Discussionmentioning
confidence: 58%
“…The anticancer activity of ursolic and oleanolic acids has been established against various cell lines [ 64 ]. Cai et al found that ursolic acid inhibited the migratory activity of CaKi-1 cells, reduced the ability of CaKi-1 cells to form renal tubules, and reduced the volume and weight of CaKi-1 cell tumors [ 65 ]. Vilkickytė et al investigated the fractions of triterpene compounds isolated from lingonberry fruit ( Vaccinium vitis-idea L.) and found that the fraction consisting of oleanolic and ursolic acids exhibited the strongest cytotoxic activity against the CaKi-1 cell line (the EC 50 was 4.5 µg/mL) [ 66 ].…”
Section: Resultsmentioning
confidence: 99%